2005
DOI: 10.1007/s10103-005-0340-3
|View full text |Cite
|
Sign up to set email alerts
|

Laser acupuncture induced specific cerebral cortical and subcortical activations in humans

Abstract: As recent studies demonstrated, acupuncture can elicit activity in specific brain areas. This study aims to explore further the central effect using laser acupuncture. We investigated the cerebral effects of laser acupuncture at both acupoints GB43 with functional magnetic resonance imaging (fMRI). As a control condition the laser was mounted at the same acupoints but without application of laser stimulation. The group results showed significant brain activations within the thalamus, nucleus subthalamicus, nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 26 publications
5
39
0
3
Order By: Relevance
“…Whereas needle acupuncture studies have shown activation and deactivation of the somatosensory cortex [3,4,6,7,[11][12][13][14], superficial needling and laser intervention appear to stimulate cortical and subcortical structures other than the somatosensory cortex [11,19,20]. This is consistent with the observation that low intensity laser stimulation does not produce a skin sensation.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Whereas needle acupuncture studies have shown activation and deactivation of the somatosensory cortex [3,4,6,7,[11][12][13][14], superficial needling and laser intervention appear to stimulate cortical and subcortical structures other than the somatosensory cortex [11,19,20]. This is consistent with the observation that low intensity laser stimulation does not produce a skin sensation.…”
Section: Introductionsupporting
confidence: 65%
“…There have been many studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] some of which have involved functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) of the brain effects of needle acupuncture. Some neuroimaging and neuroendocrine studies have suggested that needle acupuncture affects hypothalamic as well as extrahypothalamic functions and modulates mood [3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…1 Based on this beliefs about the causes of obesity, a variety of acupoints is targeted in the treatment of obesity, including Neiguan (P6), Fenglong (St40), Liangmen (St 21), Guanyuan (R4), Zusanli (St36), Tianshu (St25), and Quchi (LI11), where P refers to a pericardium, St to stomach, R to Ren, and LI to large intestine meridians. 15,16 Many people today understand that diet and exercise can help them lose weight, but the biggest problem they come across is how to suppress their appetite. 9 Studies have shown that stimulating certain acupuncture points on the human body can raise the serotonin levels and also excite the vagal nerve, both of which may reduce appetite.…”
Section: Introductionmentioning
confidence: 99%
“…Needle studies describe consistently the involvement of the sensory cortex. 13,40,41,[52][53][54] As the lowintensity laser has non-nociceptive properties, activation of the primary somatosensory cortex was not recorded for all acupoints except LR 8, which was stimulatory of primary sensory and motor cortices. The significance of this is not known.…”
Section: Laterality Of Stimulation and Sensorimotor Cortical Stimulationmentioning
confidence: 98%